2022
DOI: 10.1002/eat.23753
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in anorexia nervosa and its modifiers: A meta‐regression study

Abstract: Objective: Adiponectin, which is secreted from adipose tissue, is a protein hormone.Although a large body of studies have found that circulating adiponectin levels increase in anorexia nervosa (AN) and caloric restriction, the effect of subtypes of AN and modifiers of adiponectin in AN are not yet known.Methods: A systematic search of electronic databases was performed using the search terms "adiponectin," "anorexia nervosa," and "eating disorder" up to January 2021. All studies published in peer-reviewed jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…It is a protein secreted by adipose tissue and is inversely related to BMI. As in other forms of underweight and cachexia, adiponectin is elevated in anorexia [ 37 , 38 , 39 , 40 , 41 , 42 ] and has been reported to be lower, similar, or higher in other forms of eating disorders compared with controls [ 38 , 43 ] and decreases with refeeding, as expected [ 44 ]. The role of adiponectin in the regulation of appetite and food intake remains unclear [ 45 ].…”
Section: Resultssupporting
confidence: 62%
“…It is a protein secreted by adipose tissue and is inversely related to BMI. As in other forms of underweight and cachexia, adiponectin is elevated in anorexia [ 37 , 38 , 39 , 40 , 41 , 42 ] and has been reported to be lower, similar, or higher in other forms of eating disorders compared with controls [ 38 , 43 ] and decreases with refeeding, as expected [ 44 ]. The role of adiponectin in the regulation of appetite and food intake remains unclear [ 45 ].…”
Section: Resultssupporting
confidence: 62%
“…These aforementioned symptoms are not observed in constitutionally thin people and may therefore constitute the line between health and disease. Previous studies have also shown significant relationships between various inflammatory factors and adiponectin [ 15 , 24 , 44 ]. The current findings further highlight the role of heavily disturbed general body functions in AN compared to constitutional thinness.…”
Section: Discussionmentioning
confidence: 94%
“…Adiponectin levels can also be affected by the presence of eating disorders, especially AN. Two meta-analyses have confirmed significantly increased levels of adiponectin in AN compared to healthy controls [ 14 , 15 ]. However, it is not clear whether constitutional thinness (C.Thin) is associated with increased adiponectin levels compared to those of healthy controls [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although adiponectin is an appetite-regulating cytokine secreted from adipose tissue, the blood adiponectin level is negatively correlated with body mass index (BMI) and body fat mass [17]. In line with this, most studies and a recent metaanalysis reported that patients with AN exhibited hyperadiponectinemia, which is normalized during refeeding [18,19]. However, elevated blood adiponectin has been observed not only in AN patients, but also in healthy underweight young people (BMI < 18.5) [20].…”
Section: Introductionmentioning
confidence: 90%
“…In spite of this being an adipose-derived hormone, it is of interest that the blood adiponectin level is inversely correlated with BMI and body fat mass [17]. Thus, many clinical studies and reviews report that hyperadiponectinemia is frequently observed in AN patients [18,19,[39][40][41][42][43]. In studies of rodents, the blood adiponectin level was not changed by shortterm caloric restriction and/or exercise [44][45][46].…”
Section: Plos Onementioning
confidence: 99%